2013
DOI: 10.5811/westjem.2013.3.12788
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Ambulance Diversion at the Hospital and Regional Levels: Systemic Review of Insights from Simulation Models

Abstract: Introduction:Optimal solutions for reducing diversion without worsening emergency department (ED) crowding are unclear. We performed a systematic review of published simulation studies to identify: 1) the tradeoff between ambulance diversion and ED wait times; 2) the predicted impact of patient flow interventions on reducing diversion; and 3) the optimal regional strategy for reducing diversion.Methods:Data Sources: Systematic review of articles using MEDLINE, Inspec, Scopus. Additional studies identified thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Overcrowding usually occurs when the arrival rates of patients exceed an ED's capacity [1]. However, increasing the ED capacity by adding resources, for example, the number of inpatient beds and medical staff, has limitations in terms of space and budget for many hospitals [5]. Therefore, research has been conducted to improve ED operations by managing patient flows without changing or reorganizing the resources, within the budget [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Overcrowding usually occurs when the arrival rates of patients exceed an ED's capacity [1]. However, increasing the ED capacity by adding resources, for example, the number of inpatient beds and medical staff, has limitations in terms of space and budget for many hospitals [5]. Therefore, research has been conducted to improve ED operations by managing patient flows without changing or reorganizing the resources, within the budget [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Hospital closure and related ambulance diversion has been subject to extensive research and thus been widely discussed [ 15 , 16 ]. Various approaches have attempted to limit ambulance diversion [ 11 , 17 ], a multitude of potential solutions was introduced to reduce emergency department crowding [ 18 ]. Our findings from the data analysis suggest that ambulance diversion and hospital closures are frequent and their causes foreseeable.…”
Section: Discussionmentioning
confidence: 99%
“…The operations research solutions described by Hoot and Aronsky [91] consist in simulation and queueing theory. Delgado et al [94] provide a systematic review of insights from simulation models. All studies described by Delgado et al found that reducing the time admitted patients were awaiting placement into inpatient beds at the ED and the length of stay at the ED were expected to reduce ambulance diversion.…”
Section: Emergency Departmentsmentioning
confidence: 99%